ATTRACTING OF FOREIGN INVESTMENT FOR ECONOMIC DEVELOPMENT OF RUSSIA - I. G. Tyutyunnik (Финансы: теория и практика)
The article is devoted to the analysis of international cooperation in the field of attracting foreign investment for economic development of Russia. Carrying out investment activities in developing countries and States with economies in transition with their inherent political and economic instability, foreign investor runs the risk that in the event of a change of law, it may incur financial risks. The problem of free movement of the capitals and repatriation of the gained income from the territory of one state on the territory of another concerns free export of the current income of the investor (dividends, percent, a royalty, etc.); the sums paid in repayment of loans; export of initial capital investments; the money arising at elimination or the termination of investment activity, partial or full sale of capital investments; compensation received by the investor in case of withdrawal of its property; any other payments in connection with capital investments.